PERCEPTIONS, ATTITUDES, AND PRACTICES OF MIDWIVES TOWARDS THE USE OF TELEHEALTH - Avina Oktaviani Algifnita; Budi Prasetyo; Ivon Diah Wittiarika (Universitas Airlangga, 2022)
Background: The COVID-19 pandemic has led to the closure of health facilities and a decrease in the usage of contraceptives. Therefore, the government and professional organizations initiated telehealth services to improve the quality of health services and minimize the risk of COVID-19 transmission. Aims: This study explored the perceptions, attitudes, and usage of telehealth by independent midwives during the COVID-19 pandemic in Surabaya. Methods: This qualitative phenomenology study was conducted from March to April 2021, and it involved independent midwives in Surabaya. The purposive sampling technique was used to select informants, and it obtained seven informants that met the inclusion criteria. Primary data were retrieved through semi-structured in-depth interviews. Results: This is due to the influence of their age, knowledge, the intensity of previous telehealth use, gaps in technology use, availability of facilities and infrastructure, self-motivation, social support, and efforts to find solutions through telehealth. Conclusion: Five out of the seven midwives decided to continue using telehealth in their services after the pandemic because of its benefits and impacts. Midwives, professional organizations, and policymakers need to consider the use of telehealth to improve the future services